Early education curriculum a child's connection to the world - Jackman, Hilda L. (Wadsworth Cengage Learning, 2012)
"The fifth edition of Early Education Curriculum: A Child's Connection To The World focuses on the process of planning and implementing a curriculum, and setting up an inclusive child-centered environment. Guided by new research, position statements, and developmentally appropriate practice, the book helps both prospective and experienced teachers make informed decisions about curriculum content. Now in full color, the book meets the needs of a diverse range of readers, helping them to develop creative thinking and the ability to effectively apply theory to an early childhood classroom setting."--Publisher's description.